Prioritized content of Islamic television channels: an analytical study of Alhijrah TV - Kanaker, Osama (Penerbit Universiti Kebangsaan Malaysia, 2021)
In the world of media and communication, the producers of content are major contributors who create issues for an audience to think about. This content is not randomly created, but rather created based on certain agendas. This paper analyzes the content of the Alhijrah channel, a Malaysian Islamic TV. The objective of this study is to discover the prioritized Islamic content broadcast by Alhijrah TV that contributes to shaping the perception of Islam among viewers. To achieve this objective, content analysis, observation and interviews were conducted. The sample of the study was the last broadcasting season of 2020. It was found out that Alhijrah divided its programs into eight genres. The leading genre was a magazine that accounted for 46.56% of the sample, and the leading programs were the programs of the noble Qur'an. Alhijrah resorted to shopping programs that accounted for almost 17% of the Alhijrah content. Alhijrah also broadcast seven live programs that made up 16.71% of its programs. Alhijrah also broadcast limited programs of animation, drama, concert and talk show. This study recommends Islamic television channels and producers of Islamic content to align their agendas with the noble Qur'an to prioritize what Allah SWT prioritized to guide the audience to Allah SWT implementing the methods that He set for us.